The effect of replacing rubber tire waste as an alternative to aggregate on some properties of concrete (Sebha University Conference Proceedings, 2024)
The use of waste resulting from recycling rubber tires in concrete is considered one of the means to get rid of environmental pollution resulting from waste tires accumulated in front of landfills and car repair shops. From an economic standpoint, the use of recycled rubber in concrete is considered a low-cost option compared to traditional materials, especially in areas where It contains large quantities of waste tires, This solution can contribute to reducing waste disposal costs and reducing dependence on extracted natural resources, which achieves noticeable economic savings in the long term. This study aims to use waste resulting from rubber tire recycling as an alternative to fine and coarse aggregate with different replacement ratios: (10%, 15%, 20%) of fine aggregate, and (10%, 20%, 30%) of coarse aggregate. Mixed rubber aggregate with percentages of (20% and 30%) of fine and coarse aggregate. The results showed that replacing the fine aggregate with rubber by 10% and 15% reduces the concrete’s resistance to compression and tension to an acceptable extent, while replacing it by 20% significantly reduces the resistance. As for the coarse aggregate, the results showed that replacing the rubber reduces the concrete’s resistance to compression and tension compared to the reference mix. This indicates that as the percentage of replacement of rough rubber increases, the resistance decreases by a large percentage compared to the reference mixture. The use of 20% and 30% as mixture aggregate delays hardening and weakens the resistance. The results obtained showed that the greater the percentage of replacement of rough rubber in the concrete, the greater the amount of slump. This is due to the large size of rubber granules allowing the penetration of air and water, which increases the amount of slump. Increasing the percentage of rubber aggregate leads to reducing the density of concrete. Which reduces its weight.